Uncovering the Historical Traces of the Mothik: A Reconstruction of a Traditional Weapon Unique to Ponorogo: Mengungkap Jejak Historis Mothik: Rekontruksi Senjata Tradisional Khas Ponorogo - Muhammad Masrofiqi Maulana; Muchamad Arifin; Rivaldi Mahardika; Iqbal Rizki Sucahyo; Fahri Ahmad Fadhilah; Aulia Rahmad Saleh Siregar (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
The mothik is a traditional weapon typical of Ponorogo with a deep history and strong symbolic meaning, especially as a weapon of identity for the warok (warok). This weapon is specifically designed for short-range self-defense with a single-hit mechanism. The existence of the mothik has experienced sharp ups and downs. Once a trend and widely adopted by the community in the pre- and post-independence eras (1950s-1960s), its presence declined sharply and disappeared from the public sphere since the 1970s due to mass confiscation policies by law enforcement officials for security reasons. However, at the end of 2024, the momentum for its preservation was revived through the formation of the Pangreksa Mothik Ponorogo (Pramono) association. This study aims to examine the origins, physical specifications, various forms, and historical dynamics of the mothik weapon in Ponorogo using historical research methods that include heuristics, verification, interpretation, and historiography. The results show that the mothik transformed from a technical defense tool into a cultural heirloom with economic value and a prestigious symbol of Ponorogo Regency's identity.